Forces on a marine current turbine during runaway. (September 2017) - Goude, Anders; Lundin, Staffan
Graphical abstract: Highlights: During runaway, a marine current turbine overshoots the asymptotic runaway speed before settling. Numerical simulations indicate peak forces during runaway 2.7 times larger than nominal operation. Increased forces mainly due to the rotational speed, but also due to temporal lag in wake development. Abstract: A runaway marine current turbine will typically overshoot the runaway speed significantly before it settles at that speed. Numerical simulations of an experimental turbine indicate that the peak forces experienced by the turbine during runaway are up to 2.7 times those seen during nominal operation, and 2.1 times those at asymptotic runaway speed, making peak runaway force an important consideration in turbine design. The main contribution to the force increase is found to originate from the increased rotational speed, but a significant part is also due to the temporal lag in turbine wake development. A parameter study further shows that turbines with low inertia, turbines that have low losses, and turbines designed for low tip speed ratios will experience larger increases in forces.